Studi Variasi Ukuran Partikel Biosolid IPAL Pabrik Kelapa Sawit (PKS) Menggunakan Aktivator H3PO4 - Syafdika Sari Siregar; Elvi Yenie; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The untreated Biosolid Waste of POM from WWTP can be pollutants for the soil surface. The Biosolid Waste utilization through the sustainable approach of environment is by changing the waste biosolid POM from WWTP into the adsorbent. The particle size of the activated carbon biosolid POM be varied in a range, those are 100 and 120 mesh and chemically activated with H3PO4 9% as activators and physically activated using furnaces with temperatures of 500 °C for an hour. The best quality of biosolid POM as activated carbon is analyzed by water content, ash content and the absorption of iodine, in amount of 3.48%; 0.33%; 25.380 mg/g while the biosolid POM in particle size of 120 mesh were added.Keywords : Adsorbent, activated carbon, biosolid, particle size.